Individual Determinants of anti-Muslim Prejudice in the EU-15 - Kaya, Ayhan; Kayaoğlu, Ayşegül (ULUSLARARASI ILISKILER KONSEYI DERNEGI, 2017)
Visible negative attitudes towards Muslims, especially in the last decade, brought about a need to analyse anti-Muslim prejudice in detail as a cultural, political and also religious phenomenon. This article provides a micro-level quantitative analysis for 15 European Union countries using data from the World Values Survey and the European Values Survey for the period between 1994 and 2009. It is found that age, nationalism and being male have a positive impact on the predicted probability of displaying anti-Muslim prejudice while religiosity, education level, happiness in life and the size of the town have a decreasing impact. The article is expected to complement the scientific need for cross-national analysis of mass-level attitudes towards Muslims.
Keywords: Islamophobia; World Values Survey; European Values Survey; Intergroup Contact